Oil Price, Government Revenue, Export Value, and Economic Growth: Indonesia’s Case - Abimanyu, Yoopi (Jurnal Kajian Ekonomi dan Keuangan, 2016)
Oil has been one of the main sources of Indonesia’s revenue, either from government budget or balance of payments point of views. Due to supply and demand of oil in the world market, prices of oil, either ICP, Brent UK, or WTI, had been decline lately. There are three hypotheses in this paper. The first hypothesis, oil prices change has a positive relationship with the government revenue. Using correlation coefficient, it is found that prices of oil are positively correlated with government revenue in terms of income tax and non-tax revenue with relatively small value. The second hypothesis, oil prices have a positive correlation with export value. Correlation coefficient indicates that they are positively correlated with a somewhat higher value relative to the first finding. The third hypothesis is oil prices are positively correlated with economic growth in terms of GDP constant price. Using Johansen cointegration, it is found that oil prices are not cointegrated with economic growth. This implies that oil is correlated with government revenue and export value. However, it seems that for the whole economic growth, oil is not correlated to the economy, or the reduction of oil price would not necessarily translate into a decline in the economic output.